Haematological features of primary myelodysplastic syndromes (PMDS) at initial presentation: a study of 118 cases. Issue 10 (October 1983) - Juneja, S K; Imbert, M; Jouault, H; Scoazec, J Y; Sigaux, F; Sultan, C
Abstract : The haematological features of 118 cases of primary myelodysplastic syndromes (PMDS) were reviewed to see how these could be related and classified according to the recent FAB proposals. A majority of the cases were elderly who presented with a macrocytic or normocytic anaemia and reticulocytopenia. Cases of acquired idiopathic sideroblastic anaemia (AISA) usually had normal leucocyte and platelet counts, erythroid hyperplasia, marked dyserythropoiesis and more than 20% ringed sideroblasts. Cases of refractory anaemia with excess of blasts (RAEB) had frequent neutropenia and thrombopenia usually with prominent dysgranulopoiesis and dysthrombopoiesis. Refractory anaemia or refractory cytopenia appeared morphologically to be a heterogeneous group. Leukaemic transformation did not occur in any of these 16 cases of AISA whereas six of the 34 cases of RAEB transformed into acute leukaemia. It appears that the cases of PMDS present with well defined haematological features which permit recognition of different groups; these latter groups appear to be morphologically and prognostically distinct.